EDUCATIONAL ACTIONS TO PREVENT DENGUE: EXPERIENCES AND STRATEGIES WITH ELDERLY - Rosamaria Rodrigues Garcia; Vanessa Lopes Munhoz Afonso; Carolina Menezes Sinato; Filomena Neves Pereira Vieira Adduci; Regina Garcia do Nascimento; Francisco Souza do Carmo; Paulo Sérgio Pelegrino (Universidade de Santa Cruz do Sul, 2015)
Objective: Describe the activities performed on apublic specialized ambulatory care for dengue prevention among elderly. Case report: the epidemiological outlook of dengue is scaring being characterized as a public health problem. The elderly are most at risk for hospitalization and severe forms of the disease, thus health education activities are essential to improve awareness of the need to fight and prevent the disease. A Health Education project was created, evolving communication strategies to raise awareness on the issue. They were performed by a post graduate Gerontology group in activities such as interactive puppet show, myths and truths dynamic, informative folder, parody, posters, training seniors, caregivers and family members, internal and external health professionals, staff and residents of nearby long term care facilities. The materials were available in print and digital version. 2,500 elderly and 350 professionals were trained and encouraged to multiply the information and inspire adoption of preventive measures. The actions provided intergenerational interaction and empowerment of the elderly, whom trained, had the opportunity to exercise social participation and disseminate recommendations for other users. Conclusion: the project enabled the construction of knowledge through interactive educational activities that contributed to strengthen the individual and collective awareness, awareopinion leaderstothe importance of communication/education in the fight against dengue, which emphasized social responsibility in rescuing citizenship in a perspective thateach citizen is responsible for himself and for community. DESCRIPTORS: Dengue. Aged. Disease prevention. Health education.